"Reasonable adjustments" under the UK's Equality Act 2010: An enquiry into the care and treatment to patients with intellectual disabilities in acute hospital settings. Issue 6 (20th June 2019) - Redley, Marcus; Lancaster, Isabella; Pitt, Adam; Holland, Anthony; Thompson, Angela; Bradley, John R.; Glover, Gyles; Thomson, Karen; Jones, Sara; Herbert, Bernadette; Holme, Anita; Clare, Isabel C. H.
Abstract: Objectives: To understand the views of qualified medical practitioners regarding "reasonable adjustments" and the quality of the care and treatment provided to adults with intellectual disabilities when admitted to acute hospitals as inpatients. Methods: Semi‐structured interviews took place with 14 medical practitioners, seven from each of two acute hospitals, with a thematic analysis of the resulting data. Results: All 14 medical practitioners reported problems in the diagnosis and treatment of patients with intellectual disabilities. Most participants attributed these difficulties to communication problems and/or behaviours that, in the context of a hospital ward, were non‐conforming. However, a minority reported that, because they were likely to have multiple comorbid health conditions, patients with intellectual disabilities were more complex. In addition, half of all these respondents reported making little use of "reasonable adjustments" introduced to improve the quality of the care received by this group of patients. Conclusions: Medical practitioners should make better use of the "reasonable adjustments" introduced in the UK to address inequities in care and treatment received by patients with intellectual disabilities. However, training should also focus on the biomedical complexities often presented by these men and women.